Bacterial endotoxins: comparison of mitogenic, polyclonal, antibody-inducing and toxicity activities - Sourek, J; Svobodová, M; Dvorák, R; Müller, J; Sůla, K; Nouza, K (Folia microbiologica, 1991)
The mitogenic effects on mouse spleen lymphocytes were determined in a large series of commercially available and laboratory-prepared lipopolysaccharides (LPS) obtained from Escherichia, Salmonella, Serratia and Shigella species; part of these LPS preparations was chemically modified prior to testing. In order to establish whether the degree of mitogenic activity corresponds with other biological effects of these preparations, polyclonal activity, capability to induce specific antibody formation and toxicity were determined for selected LPS's with different mitogenic effects. Some of the detoxication procedures used succeeded in reducing the toxicity of LPS while preserving its high mitogenic activitione of the Fe-detoxified preparations of LPS (from the R-form of Shigella dysenteriae serovar 1) exhibited a medium-degree efficacy in all parameters studied. Generally, there was no correlation between the degree of mitogenic activity and the polyclonal and antibody-inducing activities, but in some instances polyclonal activity did correlate with the antibody-inducing activity.
Keywords: protilátky bakteriální; endotoxiny; Antibody-Producing Cells; Lipopolysaccharides; buňky produkující protilátky; pyrogeny; Mice; Endotoxins; Enterobacteriaceae; aktivace lymfocytů; zvířata; Lymphocyte Activation; králíci; Antibodies, Bacterial; lipopolysacharidy; Rabbits; Pyrogens; myši; Animals